2016
DOI: 10.1016/j.memsci.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration with self-generated RO concentrate pulse backwash in a novel integrated seawater desalination UF-RO system

Abstract: Ultrafiltration as a pretreatment for RO feedwater with enhanced UF backwash, which combines continuous with pulse backwash, was investigated in a novel UF-RO process integration. Direct supply of RO concentrate to the UF module served for UF backwash which was further enhanced with pulse backwash generated using bladder-type hydraulic accumulators. Model analysis of the hydraulic accumulator operation, which was validated via a series of field experiments, demonstrated a capability for accumulator charging di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Effective self‐adaptive RO feed pretreatment that can handle temporal variability of raw feed water quality and production demand is also likely to lead to significant reduction in the use of feed treatment chemicals while reducing the frequency of membrane cleaning and replacement. All of the above would benefit from real time monitoring of membrane fouling and mineral scaling . It is also stressed that real‐time monitoring of feed and product water quality (e.g., w.r.t emerging contaminants) and of membrane integrity would contribute to establishing effective operational strategies to mitigate fouling/scaling and toward gaining acceptability of RO for direct potable reuse applications.…”
Section: The Path To Improving Ro Desalinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective self‐adaptive RO feed pretreatment that can handle temporal variability of raw feed water quality and production demand is also likely to lead to significant reduction in the use of feed treatment chemicals while reducing the frequency of membrane cleaning and replacement. All of the above would benefit from real time monitoring of membrane fouling and mineral scaling . It is also stressed that real‐time monitoring of feed and product water quality (e.g., w.r.t emerging contaminants) and of membrane integrity would contribute to establishing effective operational strategies to mitigate fouling/scaling and toward gaining acceptability of RO for direct potable reuse applications.…”
Section: The Path To Improving Ro Desalinationmentioning
confidence: 99%
“…Current practice of membrane fouling prevention emphasizes the removal of potential foulants, prior to any RO desalting unit operations, using conventional flocculation/coagulation, disinfection (e.g., via chlorine dosing or UV pretreatment), media filters or membrane filtration (microfiltration or ultrafiltration) processes for RO feed water pretreatment. 16,32,43,48,50,51 In some cases, sodium metabisulfite, sodium bisulfite, or activated carbon may also be used for dechlorination of the RO feed to avoid RO membranes degradation due to chlorine; 52,53 it is noted, however, that the use of chlorine in RO feed is now typically avoided in modern plants. 11 These feed pretreatment processes, while effective for minimizing membrane fouling due to particulate deposition, organic adsorption, and biological growth, do not remove mineral scale precursors.…”
Section: Ro Desalinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many improvements have been developed to overcome this phenomenon by manipulating membrane structure or by enhancing the efficiency of backwashing [ 7 , 8 ]. This procedure was studied using the filtration of natural water, with a combination of surface modifications of membranes [ 9 ] or for seawater treatment [ 10 ]. Backwash understanding and optimization was studied to link the key backwash parameters and characteristics of feed water [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that they impacted the permeate flux. Gu et al (2016) incorporated the ultrafiltration with reverse osmosis in one system, in which, the UF represented the pretreatment for salt water desalination. Pulsed and continuous back washing were applied to the UF membrane, which removed the fouling without the use of chemicals.…”
Section: Membrane Filtrationmentioning
confidence: 99%